Pemanfaatan Aplikasi Microsoft Office Dalam Proses Belajar Mengajar Bagi Guru Di SDK Tilang, Desa Tilang, Kecamatan Nita - Philipus Eksan D.Rovin; Suryati Suryati; Rimasi Rimasi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research aims to introduce and train Tilang SDK teachers in utilizing Microsoft Office applications such as Word, Excel and Power Point which provide interesting features as tools in the teaching and learning process because there are some teachers who cannot use and utilize the features provided. It's in Microsoft Office. This training was carried out at SDK Tilang with the main subject being the teachers at the school because based on the results of the review there were still teachers who used monotonous teaching media, namely thematic books. Apart from that, there were several teachers who were not yet able to operate the features in Microsoft Office.This research uses a qualitative descriptive method, with the research subjects being teachers at SDK Tilang.